HUBUNGAN ANTARA MAQÄ€á¹¢ID AL-SYARÄªâ€™AH DENGAN BEBERAPA METODE PENETAPAN HUKUM (QIYÄ€S DAN SADD/FATH AL-Å»ARÄªâ€™AH) - Halim, Fatimah (Hunafa: Jurnal Studia Islamika, 2010)
This articleÂ discussesÂ theÂ relationshipÂ betweenÂ maqÄá¹£id al-syarÄ«'ahÂ withÂ severalÂ methods ofÂ  determiningÂ  the law.Â The object of theÂ studyÂ is limitedÂ to twoÂ modelsÂ of law, namely qiyÄs andÂ  sadd (fath) Â al-Å¼arÄ«'ah.Â  This problemÂ was discussed throughÂ library research byÂ usingÂ  theÂ  comparative method. The resultsÂ  showedÂ that, the method ofÂ  determination ofÂ the law,Â  eitherÂ through qiyÄs Â andÂ sadd (fatá¸¥)Â  al-Å¼ari'ahÂ  haveÂ a very close relationship withÂ maqÄá¹£id al-syarÄ«ah.Â In theÂ qiyÄsÂ  method,Â maqÄá¹£idÂ al-syarÄ«'ah is an important factor in assessingÂ the illat, whereas in theÂ method ofÂ al-Å¼ari'ah, maqÄá¹£idÂ al-syarÄ«'ahÂ  it is Â saddÂ al-Å¼arÄ«ahÂ  orÂ fathÂ al-Å¼arÄ«'ah as a determinant factor.Kata Kunci: maqÄá¹£id al-syarÄ«ah, qiyÄs, sadd al-Å¼arÄ«â€™ah, fatá¸¥ al-Å¼ariâ€™ah